Ecofisiologia de Schizolobium parahyba (Vell.) S. F. Blake em solos de Cerrado: diferenças entre solos podem modular o desenvolvimento de uma arbórea invasora? - Silva, Wesley Costa (2020)
The presence of invasive species in an ecosystem actively contributes to the loss of diversity. Invasive plants have large plasticity and intrinsic factors can influence the establishment of populations, such as the quality and the attributes of the soil. Therefore, the study aimed to verify whether Schizolobium parahyba shows better development rates in Cerrado soils with characteristics similar to its original (forest formations). Soil from semideciduous seasonal forest (FES), cerrado sensu stricto (CER) and degraded cerrado (DEG) were collected and analyzed, which differed in physical and chemical characteristics such as: pH, OM, CO, P, K, Al, Ca and granulometry. The soils were placed in polyethylene pots and placed on a bench in a greenhouse. Two seeds were planted per pot, and the whole experiment was conducted under the same environmental conditions, until the 45th day, when the emergence of plants and morphophysiological parameters were measured. Plants of S. parahyba showed better development when grown in the soil of FES in relation to the soils DEG and CER. The principal component analyzes showed discrimination among the plants grown in the three types of soil, in a more distinct way the FES group in relation to the others. The emergence of S. parahyba seedlings was lesser in the CER soil. The development of the specimens differed in several physiological and morphological parameters, affecting both the production of biomass and its allocation in different parts of the plant. From these parameters, it was possible to observe larger plants with greater vigor grown FES, and smaller and less robust plants grown in CER and DEG. Schizolobium parahyba showed better development in forest phytophysiognomy soil than in typical cerrado phytophysiognomies, which would place forest formations as one of the most endanger by invasion.